2020
DOI: 10.3390/molecules25143133
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-Anilinoquinolinylchalcone Derivatives as Potential NRF2 Activators

Abstract: Activation of nuclear factor erythroid-2-related factor 2 (NRF2) has been proven to be an effective means to prevent the development of cancer, and natural curcumin stands out as a potent NRF2 activator and cancer chemopreventive agent. In this study, we have synthesized a series of 4-anilinoquinolinylchalcone derivatives, and used a NRF2 promoter-driven firefly luciferase reporter stable cell line, the HaCaT/ARE cells, to screen a panel of these compounds. Among them, (E)-3-{4-[(4-acetylphenyl)amino]q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Additionally, the molecular docking results of some 4-quinolinyn chalcones exhibited that a structurally related small molecule is well-situated by the bound region of Keap1-Kelch and NrF2 through stable hydrogen bonds and the hydrophobic interaction (in a way similar to that depicted in Fig. 8 for silybin), which contributed to high affinity and stability between the ligand and the receptor [179]. The tested compounds are Nrf2 activators in the micromolar concentration.…”
Section: Interactions Of Curcumin With Proteins Linked To Nrf2 Activitymentioning
confidence: 68%
“…Additionally, the molecular docking results of some 4-quinolinyn chalcones exhibited that a structurally related small molecule is well-situated by the bound region of Keap1-Kelch and NrF2 through stable hydrogen bonds and the hydrophobic interaction (in a way similar to that depicted in Fig. 8 for silybin), which contributed to high affinity and stability between the ligand and the receptor [179]. The tested compounds are Nrf2 activators in the micromolar concentration.…”
Section: Interactions Of Curcumin With Proteins Linked To Nrf2 Activitymentioning
confidence: 68%
“…In order to discover the biological activity of new metabolites for future medicinal applications, 1 – 3 were tested for their cytotoxic, antibacterial, and anti-inflammatory activities. The cytotoxicity of 1 – 3 against HCC Huh7 cell line was evaluated by the resazurin assay [ 18 , 19 ], and none of the compounds showed notable activity against the growth of this cancer cell line. Furthermore, the assay for the growth inhibition of S. aureus showed that compound 1 exhibited 46%, 47%, and 93% inhibition at 50, 100, and 200 µM, respectively, while 2 displayed 24%, 42%, and 40% inhibition at 50, 100, and 200 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity assay was performed using the methods described previously [ 18 , 19 ]. Huh7 cells were used in resazurin assay (Cayman Chemical) and treated with indicated concentrations (12.5, 50.0, and 200.0 µM) of compounds for 72 h. The DMSO control was assigned 100% of relative cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…HOactivity not only degrades injurious heme, but its effector molecules possess anti-oxidative and anti-inflammatory properties of potential benefit to ARDS patients [352]. 4-Anilinoquinolinyl chalcone upregulates HO-1 expression and has beneficial anti-inflammatory and anti-oxidant properties typical of the chalcone family [353]. Novel chalcones display anti-inflammatory and anti-oxidant effects invitro and after LPS induced acute lung injury [354].…”
Section: Long Covid Diseasementioning
confidence: 99%